Is GDF-15 level associated with gestational diabetes mellitus and adverse perinatal outcomes? - Kadriye Yakut; Doğa Fatma Öcal; Filiz Halıcı Öztürk; Merve Öztürk; Yüksel Oğuz; Selcan Sınacı; Turhan Çağlar (Elsevier, 2021)
Objective: Growth differentiation factor-15 (GDF-15), the new member of transforming growth factor (TGF)-beta family, is released as a response of oxidative stress, inflammation and tissue injury. We aimed to determine GDF-15 levels in patients with Gestational Diabetes Mellitus (GDM) and the relation between GDF-15 and adverse perinatal outcomes. Materials and methods:: Forty pregnant women with GDM (receiving diet and insulin therapy) and forty healthy pregnant women as control group participated in this current study. GDF- 15 levels were analyzed by enzyme-linked immunosorbent assess kit. Results: The median serum GDF-15 level was measured higher in patients with GDM, and it was statistically meaningful (p: 0.000). Logistic regression analysis indicated that with the increase of GDF-15 level, the risk of GDM diseases increases as well. (P: 0.001, OR = 1.009; 95% CI = 1.003-1.014). There were no differences between GDF-15 levels and perinatal outcomes. Conclusion: We concluded that higher GDF-15 levels are related to GDM in the third trimester. The optimal GDF-15 cut-off value was measured as 326 pg/ml for the diagnosis of GDM with 70% sensitivity and 60% specificity in our study. Further studies are needed to show the significance of GDF-15 as a biomarker for the disease.